PUTUSAN MAHKAMAH KONSTITUSI YANG DISERTAI DENGAN PENDAPAT HAKIM BERBEDA (DISSENTING OPINION) DALAM PEMENUHAN PRINSIP-PRINSIP KEADILAN - Saleh Suat, Muammad (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
In some of its decision the Court has given a decision accompanied by the inclusion of a different opinion (dissenting opinion). However, the pattern of arrangement, objectives, and benefits for the people who need justice and legal certainty of the existence of dissinting opinion has not been set properly to satisfy the justice in society. So good in the Judicial Power Law Constitutional Law has not been mandated Nor concrete clarity to the differences of opinion among judges in formulating a decision. both in 1945 and Constitutional Law and the Constitutional Rule by law must be found to the judge of the law. This legal research using the Normative Legal penilitian type of analysis results are presented focuses on the study of literature. Legal materials in use and are grouped primary legal materials and secondary legal materials. Legal materials are then interpreted and analyzed. The results showed that the things behind Judge of the Constitutional Court issued a ruling that accompanied the opinion of different judges (dissenting opinion) are: the opinion of the judge who saw and decide a case with angles and different perceptions of quality even a different opinion of the judges, lack of roundness argument verdict, the judges Conflict of interest can be triggered also a dissenting opinion, and no consensus dijiwainya concept mandated by Pancasila. Keywords: Juridical Problems, Judge Differences, Justice.